The Role of Eastern European Immigration in Grounding the Brexit Movement - Rouighi, Meriem; Afkir, Mohamed (Faculty of Letters and Foreign Languages Department of English, 2023)
Migration has shaped Britain's economy, legislation, society, culture, and ties to the world. Britain's connection with immigration is a sensitive political and sociological issue, forcing the government to either accept immigrants as refugees or for economic benefits, or establish legislation to restrict and control it. In May 2004, the EU welcomed 10 new members from Central and Eastern Europe: The Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, and Slovenia commonly referred to as A8 and EU 8 countries. Malta and Cyprus entered the European Union without any limits on the free movement of citizens from other member states. Romania and Bulgaria, two additional Eastern and Central European nations, joined the European Union in 2007, followed by Croatia in 2013.It was the largest expansion since World War II. This was particularly significant within Britain who opened to the new member states its labour market without restriction from day one in 2004 contrary to the other member states who imposed transitional restrictions.Thanks to their free movement in Britain acquired by EU membership, their impact led to Britain’s most contentious immigration decision to leave the European Union joined in 1973.In response, this study examines the effect that led to the Brexit process. The work will be non-experimental, historical, explanatory, descriptive, comparative, and analytic, collecting and analyzing qualitative data. It utilizes scholarly articles, books, newspaper stories, and websites as credible online sources. Though the impact of EU immigration was at the center of the debates before and during the referendum fueled by politician and tabloids raising antagonism among British, the EU immigration was more utilized as a scapegoat for elections rather trying to answer the real social problems impacted by the EU immigration.